Design and validation of a scale of use of virtual academia during the COVID-19 pandemic - Mamani- Benito, Oscar (2021)
It is necessary to evaluate the virtual class environments that have been generated by the COVID-19 pandemic. In view of this, the objective was to design and validate a scale for the use of virtual academic media. The study is of an instrumental type, where the sample was conformed by 582 Peruvian university students. The scale was conformed by 10 items distributed in 2 dimensions. In order to find the validity of the content, it was considered the experts' judgment, for the validity of the construct, the exploratory and confirmatory factorial analysis, and to estimate the reliability, the Cronbach's αThe results indicate that the items received a favorable evaluation (Aiken's V > .70). Goodness-of-fit indices were satisfactory (χ2 = 24,204, df = 13; p = .001; RMR = .058; IFC = .931; TLI = .908; GFI = .957; AGFI = .931 and RMSEA = .071), and the correlation between factor 1 and 2 was significant (p < 0.05) and reliability good (α= .74; 95% CI = .70 -.77). It is concluded that the COVID-19 pandemic virtualacademia scale is a short tool and has evidence of validity and reliability.